The transformation of High School Bukit Mertajam Resource centre to national laureate Muhammad Haji Salleh resource centre - Rosman, Nabila Kamalia; Ismail, Muhammad Farhan; Salimee, Hajar Izzati; Abdul Wahab, Muhammad Daniel; Tan Zi Ye, Nik Yasirah (Universiti Teknologi MARA, Kedah, 2019)
The past conventional outlook of High School Bukit Mertajam resource centre was given a contemporary touch with the collaborative venture in which the teacher-librarians, teachers, and administrators work together to provide opportunities for the social, cultural, and educational growth of students. The transformation which not only involves the physical aspects of the resource centre but also its role unveils a new breadth of identity in the school history as well as revolutionized the traditional function of a school resource centre in Malaysia. The school resource centre’s name was taken after the name of the renowned National Laureate, Muhammad Hj Salleh, who is also a former student of High School Bukit Mertajam. He was honorably invited to officiate the school resource centre. An official ‘Prof’ mascot and the school resource centre logo which were meticulously designed and made with all its details were also introduced. To give the resource centre a new outlook, the motifs of nature in traditional craft such as ‘Pucuk Rebung’, ‘Tampok Manggis’, ‘Bunga Pecah Lapan’ and ‘Bunga Tanjung’ are carefully chosen to decorate the interior parts. Each space of the resource centre was utilized to its fullest by given its own identity and functions, mostly using recycled items. There was also a café corner for the students to unwind and relax and also ‘Dangau Ilmu’ for them to play some games such as ‘congkak’, Sahiba and chess. This is further enhanced with the rearrangements of round tables and chairs to provide a range of learning opportunities for both large and small groups as well as individuals with a focus on intellectual content, information literacy and the learner. In addition to classroom visits with teachers, the resource centre also now serves as a place for students to do independent work, use computers, use audio-visual equipment and research for materials; as well as to hold special events such as thematic exhibitions, video conference, meetings and special functions.